2022
DOI: 10.1021/acsami.2c12088
|View full text |Cite
|
Sign up to set email alerts
|

Non-autofluorescence Detection of H5N1 Virus Using Photochemical Aptamer Sensors Based on Persistent Luminescent Nanoparticles

Abstract: Fluorescence sensing is limited in practical applications owing to multiple autofluorescent substances in complex biological samples such as serum. In this paper, the luminescence decay effect of persistent luminescent nanoparticles (PLNPs) was used to avoid the interference of autofluorescence in complex biological samples, and a non-autofluorescence molecularly imprinted polymer aptamer sensor (MIP-aptasensor) was designed to detect H5N1 virus. The proposed MIP-aptasensor consists of a magnetic MIP and aptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Recently, association with the latest techniques and other materials has been another trend in this area. A non-self-fluorescent molecularly imprinted polymeric aptasensor (MIP-aptasensor) was designed to detect the H5N1 virus [ 147 ]. Aptamer-functionalized persistent luminescent nanoparticle Zn 2 GeO 4 :Mn 2+ -H5N1 coupled with a magnetic MIP can produce an intense, constant luminescent signal after identifying the H5N1 virus, which has the highly selective and sensitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, association with the latest techniques and other materials has been another trend in this area. A non-self-fluorescent molecularly imprinted polymeric aptasensor (MIP-aptasensor) was designed to detect the H5N1 virus [ 147 ]. Aptamer-functionalized persistent luminescent nanoparticle Zn 2 GeO 4 :Mn 2+ -H5N1 coupled with a magnetic MIP can produce an intense, constant luminescent signal after identifying the H5N1 virus, which has the highly selective and sensitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent luminescence nanoparticles (PLNPs), also known as long-lasting luminescence or afterglow particles, can continuously emit luminescence for hours or even days after being excited. This special feature allows detection and imaging without external illumination, which can effectively eliminate the interference of autofluorescence on imaging signals. Therefore, PLNPs exhibit great potential in biological applications ranging from biosensing/bioimaging to theranostics. However, current research on PLNPs mainly focuses on cancer tissue-targeted biosensing/imaging, , in vivo drug tracking, , and imaging-guided photodynamic therapy, and few studies in the field of biomedical implants have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Water-borne viruses pose a serious threat to public health and safety. , Among them, pathogens such as Norovirus and Rotavirus are well-known causative factors that can lead to nonbacterial gastroenteritis in humans. , The World Health Organization has estimated that millions of people worldwide die every year due to infections caused by Norovirus or Rotavirus. , However, due to the low recognition sensitivity of biological antibodies, traditional immune antigen analysis methods were difficult to meet the detection requirements for multiple types and low loads of exposed viruses in the aqueous environment. , Similarly, polymerase chain reaction (PCR)-based nucleic acid detection methods were equally difficult to satisfy the demand for high-throughput detection of multiplex exposed virus due to their low detection throughput. , Although multiplex PCR techniques have been developed for the simultaneous detection of multiplex nucleic acid sequences, the competition and interference between primer pairs make them highly susceptible to cross-interference when dealing with complex environmental media. , In addition, the high technical requirements of PCR methods, and the complex and time-consuming amplification process make it difficult to meet the demand for immediate detection in the field of environmental analysis . Therefore, there are severe barriers to the application of traditional antigen analysis and nucleic acid detection methods for the detection of viruses exposed to the aqueous environment.…”
mentioning
confidence: 99%
“…W ater-borne viruses pose a serious threat to public health and safety. 1,2 Among them, pathogens such as Norovirus and Rotavirus are well-known causative factors that can lead to nonbacterial gastroenteritis in humans. 3,4 The World Health Organization has estimated that millions of people worldwide die every year due to infections caused by Norovirus or Rotavirus.…”
mentioning
confidence: 99%